Extraction, identification of chemical constituents, and in vitro evaluation against cells and bacterial pathogens of the leaves of Polyalthia rumphii - Ismail Zainol (Tanjung Malim, 2024)
Extraction, identification of chemical constituents, and in vitro evaluation against cells and bacterial pathogens of the leaves of Polyalthia rumphii by Ismail Zainol